Estudos das interações do peptídeo antimicrobiano Polybia MP1 com membranas modelo: mecanismo de ação e especificidade - Slade, Natália Bueno Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Bioactive peptides are of high interest as substitutes of conventional drugs since some of them present antimicrobial, antifungal and/or anticancer action. They are predominantly cationic and it has been shown that their activity is modulated by electrostatic interactions, hydrophobic contributions and the elastic features of the membranes their target. The mastoparan peptide Polybia MP1 (MP1) possesses two acidic residues (D2 and D8) and three basic ones (K4, K5 and K11), which together with the amidation of the C-terminal confers to it a relatively low net charge Q=+2. In this thesis, we analyzed the importance of the MP1 amino acid sequence, charge and hidrophobicity to the interaction with distinct model membranes, since the presence of acidic residues is a rare characteristic among the bioactive peptides and, beyond this, MP1 presents high antimicrobial and anticancer activities without being hemolytic. In search of understand its specificity and mechanism of action for bacteria and cancer cells, the activity and affinity of MP1 was assessed through circular dichroism and fluorescence spectroscopy, electrophoretic and dynamic light scattering measurements, and confocal microscopy. These techniques allowed the observation of the peptide structuration, the peptide partitioning from water to the model membranes interface, the peptide lytic activity, and the liposome aggregation due to peptide addition. From this, it was possible estimate the energetic contributions involved in the system, besides the dimension of the damages caused by MP1 on the membranes surface. MP1 showed that its low net charge and the presence of two acidic residues play an important role in modulating its structuration and activity in a wide range of lipid compositions, by equilibrating electrostatic and non-electrostatic contributions giving basis to understand its action as bioactive...

Peptídeos bioativos são de grande interesse como substitutos de antibióticos e quimioterápicos convencionais já que, alguns deles apresentam atividades antimicrobiana, antifúngica e/ou anticâncer. Eles são predominantemente catiônicos e sua atividade tem se mostrado ser modulada por interações eletrostáticas, contribuições hidrofóbicas e por características elásticas da membrana, o seu alvo. O peptídeo mastoparano Polybia MP1 (MP1) possui dois resíduos ácidos (D2 e D8) e três resíduos básicos (K4, K5 and K11), que somados ao C terminal amidado conferem a ele uma carga elétrica líquida relativamente baixa, Q= +2. Nesta tese, foi analisada a importância da sequência de aminoácidos do MP1, da sua carga elétrica líquida e da sua hidrofobicidade média na interação com distintas membranas modelo, já que a presença de resíduos ácidos é rara dentre os peptídeos bioativos e além disto, o MP1 apresenta elevadas atividades antimicrobiana e anticâncer sem ser hemolítico. Para entender a sua especificidade e o seu mecanismo de ação em células bacterianas e de câncer, a atividade e a afinidade do MP1 foi acessada através de espectroscopia de fluorescência e de dicroísmo circular, medidas de potencial eletrocinético e de espalhamento de luz dinâmico e microscopia confocal. Estas técnicas permitiram a observação da estruturação do peptídeo, da sua partição da água para a interface de membranas modelo, da sua atividade lítica e da agregação dos lipossomos devido a sua adição. Assim, foi possível estimar as contribuições energéticas envolvidas no sistema além das dimensões dos danos causados pelo MP1 na superfície da membrana. MP1 mostrou que sua baixa carga elétrica líquida e a presença de dois resíduos ácidos na sua sequência de aminoácidos apresentam um papel importante em modular a sua estruturação e a sua atividade em uma ampla gama de composições lipídicas. Isso é atribuído...
Keywords: Biologia molecular; Biofísica; Peptídeos antobióticos; Dicronísmo circular; Microscopia confocal; Membranas (Biologia)